Loading effect of aluminum hydroxide onto the mechanical, thermal conductivity, acoustical and burning properties of the palm-based polyurethane composites - Nor Rabbi’atul ‘Adawiyah Norzali; Khairiah Haji Badri; Mohd Zaki Nuawi (Universiti Kebangsaan Malaysia, 2011)
Effects of aluminium hydroxide (ATH) addition on the properties of palm-based polyurethane composites were investigated. The hybrid composites were prepared by mixing 10 wt% of oil palm empty fruit bunch fiber (EFB) with ATH at varying amount of 2, 4 and 6 wt% of the overall mass of the resin. The compression stress and modulus gave the highest values of 575 and 2301 kPa, respectively at 2 wt% loading of ATH. The compression stress and modulus decreased drastically at 4 wt% (431 kPa and 1659 kPa, respectively) and further decreased at 6 wt% ATH (339 and 1468 kPa, respectively). However, the burning rate is inversely proportional to the loading percentage where the highest burning rate was observed at 2 wt% ATH. Sound absorption analysis indicated a large absorption coefficient at high frequency (4000 Hz) for all samples. The highest absorption coefficient was obtained from PU-EFB/ATH with 4 wt% ATH.